Determination of 13 Aminoglycoside Residues in Milk by Weak Cation Exchange Solid Phase Extraction Coupled with Ultra-high Performance Liquid Chromatography-Tandem Mass Spectrometry - HE Jinlin, SHEN Luying, SUN Ting, FU Jianwei, YAN Lijuan, XU Dunming (Shipin Kexue)
In this study, a method based on weak cation exchange (WCX) solid phase extraction (SPE) coupled with ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) was developed for the simultaneous determination of 13 aminoglycoside (apramycin, amikacin, paromomycin, hygromycin B, ribostamycin, kanamycin, streptomycin, gentamicin C1, dihydrostreptomycin, tobramycin, spectinomycin, neomycin and micronomicin) residues in milk. Samples were extracted using a mixture of ammonium acetate buffer solution and acetonitrile, and purified using a WCX SPE column. Chromatographic separation was achieved using a SILICA SG80 column with gradient elution using a mobile phase made up of 0.1% formic acid aqueous solution and acetonitrile. Detection was accomplished using an electrospray ionization source (EIS) in the positive ion mode, and quantification was carried out using a matrix-matched external standard method. Excellent linear relationships were observed for the 13 aminoglycosides in the concentration range of 5.0-500.0 ng/mL (R2 ≥ 0.998 3). The limit of detection (LOD) for hygromycin B, ribostamycin, streptomycin, tobramycin, and dihydrostreptomycin were 3 μg/kg, and the limit of quantification (LOQ) were all 10 μg/kg for these aminoglycosides. For apramycin, amikacin, paromomycin, kanamycin, gentamicin C1, micronomicin, neomycin and spectinomycin, the LODs and LOQs were 15 and 50 μg/kg, respectively. The recovery rates of milk spiked at 1 ×, 2 × and 5 × LOQ levels were 73.8%–107.4%, with relative standard deviation (RSD) of 1.0%–9.8%. This developed method is sensitive, simple, stable, and suitable for the determination of these 13 aminoglycoside residues in milk.